2011
DOI: 10.1007/978-3-642-21726-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Important Places in People’s Lives from Cellular Network Data

Abstract: Abstract. People spend most of their time at a few key locations, such as home and work. Being able to identify how the movements of people cluster around these "important places" is crucial for a range of technology and policy decisions in areas such as telecommunications and transportation infrastructure deployment. In this paper, we propose new techniques based on clustering and regression for analyzing anonymized cellular network data to identify generally important locations, and to discern semantically-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
259
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(267 citation statements)
references
References 17 publications
2
259
0
6
Order By: Relevance
“…relevance. To solve the aforementioned issue, Isaacman et al [19] have proposed a technique based on clustering and regression to identify important places then assign them a semantic such as home and work. By contrast, Csaji et al [12] have combined principal component analysis with clustering to robustly identify home and work places.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…relevance. To solve the aforementioned issue, Isaacman et al [19] have proposed a technique based on clustering and regression to identify important places then assign them a semantic such as home and work. By contrast, Csaji et al [12] have combined principal component analysis with clustering to robustly identify home and work places.…”
Section: Related Workmentioning
confidence: 99%
“…In Figure 1 we report a small sample for each kind of recorded activity accompanied by a mobility trace that comes from combining the CDR entries. One of the advantages of this dataset with respect to other datasets [17,10,19,3,12] is the chance to leverage the Internet access data for purposes of mobility pattern analysis [4]. Although CDRs are rich sources for studying and analyzing human activities in different fields, they have two significant drawbacks as to providing location information.…”
Section: Call Detail Records Datasetsmentioning
confidence: 99%
“…The preprocessing stage also excludes geotags related to users' residences and work places, because of the possible bias for the unvisited PoIs nearby these locations. The two locations can be identified by either recurring time-of-day patterns of each user [1], [2], or time-spending probability models [3], [4], [5].…”
Section: Inference Of Visited Poismentioning
confidence: 99%
“…The authors of [1], [3], [4] showed that having hold of even anonymized call record details enables inference of user identities as well as the users' most frequently visited locations. Moreover, the authors of [23], [5] shows that having even a vague knowledge of person's home or work addresses can identify the person and personal beliefs, preferences and behavioral aspects.…”
Section: Related Workmentioning
confidence: 99%
“…We attempt to automatically attach a label to invisible clusters by applying a simple time-of-day-based heuristic, similar to the one suggested in [2], in order to identify clusters that appear in places such as "home" or "work". To do so, we first aggregate the coverage of all clusters that insist on the same location.…”
Section: A Differential Cluster Analysismentioning
confidence: 99%